Asthma in the elderly: The role of exhaled nitric oxide measurements - Columbo, Michele (2013)
Asthma in the elderly is poorly understood because only a small minority of asthma studies have investigated this patients group. Fractional Exhaled Nitric Oxide (FENO) has been extensively studied in children and adults with asthma, but little is known about FENO in elderly asthmatics. We studied the role of serial measurements of FENO in elderly subjects with asthma. Thirty stable asthmatics 65 years old and older were followed for one year with evaluations at baseline and every three months. We looked for associations between FENO and subjects’ demographics, comorbidities, asthma treatment, spirometric values and Asthma Control Test (ACT) scores. FENO was not elevated in our study subjects throughout the study period (mean < 30 ppb). FENO significantly increased and FEV1% decreased between first and last study visit, while ACT scores and steroid dose remained unchanged. No significant correlation was found between FENO and FEV1/FVC, other spirometric values, inhaled steroid dose or ACTscores at any time point. No associations of FENO were found with age, sex, Body Mass Index (BMI), atopic status, disease duration, presence of rhinitis or gastroesophageal reflux disease (GERD), or other medications used. Moderate asthma exacerbations did not consistently cause an increase of FENO. In stable elderly asthmatic patients, FENO was not elevated and did not correlate with subjects’ demographics, comorbidities, treatment, symptoms or spirometric values. Routine measurements of FENO may not be clinically valuable in elderly asthmatics.